HUBUNGAN KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN PADA KONSUMEN DI PT. INASA LAFACOS: (Studi Kasus Pada Konsumen Kelapa Gading) - Siregar, Yuli Astuti; Sinaga, Sautman; Tarigan, Lukas (Universitas Kristen Indonesia, 2016)
The research was carried out in PT. Inasa Lafacos to know the relationship of quality of service and trust of customer loyalty on all parts of the consumer at PT. Inasa Lafacos. As for the purpose of this research is to know the relation of quality service to customer loyalty, loyalty towards the trust relationship customers in all parts of the consumer at PT. Lafacos Inasa. The research is descriptive-correlation with sample as much as 97 of the consumer and the data were analyzed using analysis of Rank Spearman. The results of this study suggest that (1) there is a significant relationship between the quality of service of customer loyalty on the whole consumer PT. Inasa Lafacos. This is attempted with the obtained t hitung (27.809) greater than t tabel (1,985). (2) There is a significant relationship between confidence in the loyalty of customers in all parts of the consumers of PT. Inasa Lafacos. This is attempted with the obtained t hitung (13.105) greater than t tabel (1,985). Based on the results of the research, it can be concluded that the overall quality of service and trust have better relationship towards customer loyalty, then the company should further increase as do concern employees against customers, employees can meet consumer complaints properly and also employees can serve consumers well. Need for improved performance of employees at PT. Inasa Lafacos by providing training (Traning) so that employees can improve or master the skills and techniques against the implementation of a particular work. PT. Inasa Lafacos need to do a survey to consumers by way of providing a questionnaire or interview is directly related to the perceived satisfaction of consumers.